Transformative Social Studies Education Under the ‎Merdeka Belajar Framework: Activity Theory and the ‎Negotiation of Local Wisdom Knowledge in ‎Multicultural Classrooms - Edi Susrianto Indra Putra; A. Muthalib (JPI: Jurnal Pustaka Indonesia, 2026)
This study examines how Activity Theory (AT) provides an analytical framework for understanding the transformative role of Social Studies education under Indonesia's Merdeka Belajar curriculum, specifically in negotiating local wisdom knowledge within multicultural classrooms. Drawing on a qualitative case study design involving twelve Social Studies teachers across three junior high schools in Riau Province, data were gathered through semi-structured interviews, classroom observations, and document analysis. Thematic analysis reveals that the six components of Engeström's expanded Activity System; subject, tools, object, rules, community, and division of labour,operate as dynamic mediators through which local wisdom (kearifan lokal) is contested, validated, and repositioned within diverse epistemic communities. The Merdeka Belajar framework's emphasis on student autonomy, the Profil Pelajar Pancasila, and Project-Based Learning created enabling conditions for culturally sustaining pedagogies, yet systemic tensions persisted between standardized national assessment and the fluid nature of indigenous knowledge. The study contributes a theoretically grounded, empirically situated model for integrating local wisdom into Social Studies under Merdeka Belajar, with implications for multicultural curriculum design, teacher professional development, and education policy in pluralistic societies.